Unprecedented High Probe-Reported Polarity of Deep Eutectic Solvents Composed of Lanthanide Salts and Urea - Anushis Patra; Vaishali Khokhar; Siddharth Pandey (Liquids)
Deep eutectic solvents (DESs) have emerged as viable alternatives to toxic organic solvents. The most intriguing aspect of these solvents is perhaps the widely varying physicochemical properties emerging from the changes in the constituents that form DESs along with their composition. Based on the constituents, a DES can be hydrophilic/polar or hydrophobic/non-polar, rendering a vastly varying spectrum of polarity a possibility. DESs formed by mixing urea (U) with hydrated lanthanide salts, lanthanum nitrate hexahydrate (La : U), cerium nitrate hexahydrate (Ce : U), and gadolinium nitrate hexahydrate (Gd : U), respectively, exhibit very high polarity as manifested via the probe-reported empirical parameters of dipolarity/polarizability (π*). The highest π* of 1.70 exhibited by the DES (Gd : U) in a 1 : 2 molar ratio is unprecedented. The π* ranges from 1.50 to 1.70 for these DESs, which is almost the highest reported for any solvent system. The π* decreases with an increasing amount of urea in the DES; however, the anomalous trends in H-bond donating acidity (α) and H-bond accepting basicity (β) appear to be due to the hydrated water of the lanthanide salt. The emission band maxima of the fluorescence probe of the “effective” dielectric constant (εeff) of the solubilizing media, pyrene-1-carboxaldehyde (PyCHO), in salt-rich DESs reflect higher cybotactic region dipolarity than that offered by water. Probe Nile red aggregates readily in these DESs to form non-fluorescent H-aggregates, which is a characteristic of highly polar solvents. The behavior of probe pyranine also corroborates these outcomes as the (lanthanide salt : urea) DES system supports the formation of the deprotonated form of the probe in the excited state. The (lanthanide salt : urea) DES system offers solubilizing media of exceptionally high polarity, which is bound to expand their application potential.